A clinical case of multidrug-resistant tuberculosis complicated by esophageal-pulmonary fistula in a palliative patient - Raznatovska, O. M.; Petrenko, V. I.; Shalmin, O. S.; Yasinskyi, R. M.; Fedorets, A. V.; Svitlytska, O. A.; Разнатовська, Олена Миколаївна; Петренко, В. І.; Шальмін, Олександр Самуілович; Ясінський, Роман Миколайович; Федорець, Андрій Васильович; Світлицька, Оксана Анатоліївна (My University, 2023)
We present our own observation of the multidrug-resistant tuberculosis course case, complicated by esophageal-pulmonary fistula, in a palliative patient who was treated in the Pulmonary Tuberculosis Department No. 2 of the Zaporizhzhia Regional Phthisio-pulmonology Clinical Treatment and Diagnostic Center. An esophago-pulmonary fistula in the patient with multidrug-resistant tuberculosis was detected in the area of the right upper lobectomy, wich was perfomed 8.5 years ago. The patient was on palliative treatment for almost 6 years before hospital admission when a tubercular esophago-pulmonary fistula was diagnosed. The patient was admitted to the hospital in serious condition, which significantly worsened over the course of a month. A decision was made to perform a computed tomography of the chest cavity (Сhest CT) as the patient's cough and chest pain were associated with liquid food intake. Esophageal-pulmonary fistula was detected on the Chest CT as a linear air defect of the esophageal wall up to 1.5 mm, which conjugates with the cavern in the upper lobe of the right lung. The small size of the esophageal-pulmonary fistula (1.5 mm) indicates the timeliness of its detection. In the presented case, the patient is on palliative treatment. Therefore, in order to prevent the progression of the esophageal-pulmonary fistula, feeding through a nasogastric tube and antibiotic therapy were prescribed. Thus, if a palliative patient with multidrugresistant tuberculosis has a paroxysmal cough that occurs during or immediately after eating, the use of Chest CT is relevant for the timely diagnosis of eso phagealpulmonary fistula. If such a fistula is diagnosed, it is necessary to use parenteral feeding and antibiotic therapy. Представлено власне спостереження перебігу туберкульозу з множинною лікарською стійкістю, ускладненого езофагопульмональною норицею, у паліативного пацієнта, який перебував на лікуванні у відділенні легеневого туберкульозу № 2 Запорізького регіонального фтизіопульмонологічного клінічного лікувально-діагностичного центру. Езофагопульмональну норицю виявлено в ділянці проведеної 8,5 року тому правобічної верхньочасткової лобектомії. На паліативному лікуванні пацієнт перебував майже 6 років до госпіталізації у стаціонар, коли була діагностована туберкульозна езофагопульмональна нориця. Пацієнта госпіталізовано у тяжкому стані, який значно погіршився протягом місяця. З огляду на те, що кашель та біль у грудній клітці були пов’язані з прийомом рідкої їжі, прийнято рішення провести комп’ютерну томографію органів грудної порожнини. Езофагопульмональна нориця мала вигляд лінійного повітряного дефекту стінки стравоходу розміром до 1,5 мм, який сполучався з каверною у верхній частці правої легені. Незначні розміри езофагопульмональної нориці вказують на вчасність її виявлення. Пацієнт перебуває на паліативному лікуванні, тому для запобігання прогресуванню езофагопульмональної нориці йому призначено годування крізь назогастральний зонд і антибіотикотерапію. За наявності у паліативного пацієнта з туберкульозом із множинною лікарською стійкістю нападоподібного кашлю, що виникає під час або відразу після їди, для вчасної діагностики езофагопульмональної нориці слід провести комп’ютерну томографію органів грудної порожнини. У разі виявлення такої нориці застосовують парентеральне годування і антибіотикотерапію.
Клінічний випадок туберкульозу з множинною лікарською стійкістю, ускладненого езофагопульмональною норицею, у паліативного пацієнта
Keywords: Multidrug-resistant tuberculosis; esophageal-pulmonary fistula; palliative care; туберкульоз із множинною лікарською стійкістю; езофагопульмональна нориця; паліативна допомога